2022
DOI: 10.1002/gea.21907
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing of chalkstone used in medieval buildings in the Eastern Duchy of Normandy (10th−14th centuries) through geological and geochemistry analyses

Abstract: The provenance of medieval building stones links historic constructions with their quarrying areas, thereby revealing medieval trade routes and the spatial organization of past societies. In northern France, the Duchy of Normandy played a significant role in the medieval history of Europe, situated at the centre of the disputes between the English and French kingdoms. However, the historical documentation from this period is scarce, particularly in terms of the quarrying industry. Our study aims to define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…Historical works revealed that the Caumont quarrying area was active from the Middle Ages to 1906 CE, supplying stone for buildings located along the lower Seine valley (Dujardin, 2004(Dujardin, , 2006Lardin, 1998Lardin, , 2016. Recently, geoarchaeological studies suggested that Caumont provided stones during the 10th-14th centuries, for buildings located 40 km away from the quarry site (Ballesteros et al, 2022). This provision area, larger than what is known for medieval quarries, was facilitated by the fluvial mean of transport along the Seine.…”
Section: Settingsmentioning
confidence: 99%
“…Historical works revealed that the Caumont quarrying area was active from the Middle Ages to 1906 CE, supplying stone for buildings located along the lower Seine valley (Dujardin, 2004(Dujardin, , 2006Lardin, 1998Lardin, , 2016. Recently, geoarchaeological studies suggested that Caumont provided stones during the 10th-14th centuries, for buildings located 40 km away from the quarry site (Ballesteros et al, 2022). This provision area, larger than what is known for medieval quarries, was facilitated by the fluvial mean of transport along the Seine.…”
Section: Settingsmentioning
confidence: 99%